Impact of Corporate Governance on Social Responsibility: A Case of Nepalese Commercial Banks - Khatri, Guarav Jung; Giri, Jamuna; Bhatta, Kabita; Rawal, Kabita; Rawat, Ramesh (Nepalese Journal of Economics, 2024)
This study examines the impact of corporate governance on social responsibility in the context of Nepalese commercial banks. Legal corporate social responsibility and philanthropic corporate social responsibility are selected as the dependent variables. The selected independent variables are board size, independent directors, audit committee size, female directors, foreign ownership, and government ownership. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on social responsibility in the context of Nepalese commercial banks.The study showed that board size has a positive impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that larger the board size, higher would be the legal corporate social responsibility and philanthropic corporate social responsibility. Similarly, independent directors has a positive impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that increase in independent directors on the board leads to increase in legal corporate social responsibility and philanthropic corporate social responsibility. Likewise, audit committee size has a positive impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that increase in audit committee size leads to increase in legal corporate social responsibility and philanthropic corporate social responsibility. Further, female directors has a positive impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that increase in female directors leads to increase in legal corporate social responsibility and philanthropic corporate social responsibility. In addition, foreign ownership has a negative impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that higher the foreign ownership, lower would be the legal corporate social responsibility and philanthropic corporate social responsibility. Likewise, government ownership has a positive impact on legal corporate social responsibility and philanthropic corporate social responsibility. It indicates that higher the government ownership, higher would be the legal corporate social responsibility and philanthropic corporate social responsibility.